Molecular characterization of hybrid virulence plasmids in ST11-KL64 KPC-2-producing multidrug-resistant hypervirulent Klebsiella pneumoniae from China - Zhang, Fushan; Li, Leyuan; Zhao, Yuxin; Dong, Huiyue; Zhao, Buhui; Zhao, Xiaoyu; Xia, Ziwei; Chi, Leizi; Wang, Yan; Li, Ruichao; Qin, Shangshang; Fu, Xiangjing (Frontiers in Microbiology, 2024)
Carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-HvKP) strains combining virulence and multidrug resistance (MDR) features pose a great public health concern. The aim of this study is to explore the evolutionary characteristics of virulence in CR-HvKP by investigating the genetic features of resistance and virulence hybrid plasmids. The resistance and virulence phenotypes were determined by using antimicrobial susceptibility testing and the mouse bacteremia infection model, respectively. Plasmid profiles were investigated by S1 nuclease pulsed-field gel electrophoresis (S1-PFGE) and Southern blotting, conjugation assay, and whole genome sequencing (WGS). Bioinformatics tools were used to uncover the genetic features of the resistance and virulence hybrid plasmids. Two ST11-KL64 CRKP clinical isolates (KP18-3-8 and KP18-2079), which exhibited enhanced virulence compared with the classic CRKP, were detected positive for blaKPC-2 and rmpA2. The virulence level of the hypermucoviscous strain KP18-3-8 was higher than that of KP18-2079. S1-PFGE, Southern hybridization and WGS analysis identified two novel hybrid virulence plasmids in KP18-3-8 (pKP1838-KPC-vir, 228,158 bp) and KP18-2079 (pKP1838-KPC-vir, 182,326 bp), respectively. The IncHI1B/repB-type plasmid pKP1838-KPC-vir co-harboring blaKPC-2 and virulence genes (rmpA2, iucABCD and iutA) but lacking type IV secretion system could transfer into non-hypervirulent ST11 K. pneumoniae with the assistance of a helper plasmid in conjugation. The IncFII/IncR-type virulence plasmid pKP18-2079-vir may have been generated as a result of recombination between a typical pLVPK-like virulence plasmid and an MDR plasmid.Our studies further highlight co-evolution of the virulence and resistance plasmids in ST11-CRKP isolates. Close surveillance of such hybrid virulence plasmids in clinical K. pneumoniae should be performed.